Respons Audiens terhadap Jenis Alih Kode dalam Video Pembelajaran Bahasa Arab di Kanal YouTube Arab Podcasts - Abqari, Rafid Gastiadirrijal Muhammad; Supriadi, Rinaldi; Khalid, Shofa Musthofa (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to analyze the cognitive responses and processing fluency of audiences toward intra-sentential, inter-sentential, and tag-switching code-switching on the YouTube channel "Arab Podcasts". Employing a descriptive qualitative design, data were collected via Stimulated Recall Interviews with three selected participants (aged 21–35) and analyzed using Greenwald's Cognitive Response Theory and the Processing Fluency framework. The findings indicate that inter-sentential code-switching elicits a dual response: it causes focus distraction due to violated language expectations in some audiences, yet enhances affective comfort in others. Intra-sentential code-switching triggers the highest cognitive load, leading to initial disfluency; however, this can be mitigated through visual aids. Conversely, tag-switching demonstrates the highest level of processing fluency and functions effectively as a discourse marker. It is concluded that tag-switching serves as the safest instructional strategy, whereas other types of code-switching require visual support to prevent cognitive overload. These results provide practical guidelines for educators to balance linguistic use with cognitive comfort in digital learning environments.